Bimbingan Mental Spiritual Terhadap Perubahan Perilaku Negatif Remaja (Studi Kasus Panti Asuhan Yatim Putra Islam Yogyakarta) - Zukhrufatunnisa' (Medan Resource Center, 2022)
The aim of this study is to identify the forms of negative behavior exhibited by adolescents at the Yatim Putra Islam Orphanage in Yogyakarta and to understand how the mental and spiritual guidance concept applied by the orphanage influences changes in the children's negative behavior. This study is a qualitative research. It aims to explain phenomena and present them as findings. The results of the study indicate that: (1) the forms of negative behavior exhibited by the clients include negative behavior towards caregivers, negative behavior towards peers, negative behavior towards the community, as well as issues with discipline and responsibility; (2) the influence of mental and spiritual guidance on changing the negative behavior of adolescents at the Putra Islam Orphanage is achieved through the practice of obligatory worship and the habituation of sunnah worship; (3) the forms of handling juvenile delinquency at the Yatim Putra Islam Orphanage include social interventions with efforts to address clients' problems, encompassing both preventive and curative measures.